REPRESENTATIONAL SYSTEM SORT TECHNIQUE TO TEACH ENGLISH READINGCOMPREHENSION OF NARRATIVE TEXTS - Ariyanti, Ika Mella; ., Sudarsono; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The research was conducted to investigate the effectiveness of Representational System Sort (RSS) technique to teach English reading comprehension of narrative texts to Year-10 students of â€œSMAN 3 Pontianakâ€ in Academic Year 2014/2015. The research method is a quasi-experimental research with one group as experimental group and another group as the control group. The research findings show the mean score interval of pre-test and post-test for experimental group is 9.63. The mean score interval of pre-test and post-test for control group is 3.46. It means that the interval score of experimental group is higher than the control group, and the studentsâ€™ ability increased significantly after the treatments. The obtained effect size is 0.60 and be categorized as moderate. Therefore, the effectiveness of RSS technique to teach English reading comprehension of narrative texts to Year-10 students of â€œSMAN 3 Pontianakâ€ in Academic Year 2014/2015 is moderate. Keywords: RSS, Reading Comprehension, Narrative Texts. Abstrak: Penelitian ini dilakukan untuk menemukan tingkat efektifitas dari teknik Representational System Sort (RSS) untuk mengajarkan membaca komprehensif teks naratif dalam mata pelajaran Bahasa Inggris pada siswa kelas 10 â€œSMAN 3 Pontianakâ€ tahun ajaran 2014/2015. Metode yang digunakan dalam penelitian ini adalah penelitian quasi-eksperimen dengan satu kelompok sebagai kelompok eksperimen dan kelompok lainnya sebagai kelompok kontrol. Hasil dari penelitian ini menunjukkan bahwa interval nilai rata-rata pre-test dan post-test kelompok eksperimen adalah 9,63 sedangkan interval nilai rata-rata pre-test dan post-test kelompok kontrol adalah 3.46. Hal ini menunjukkan bahwa nilai interval kelompok eksperimen jauh lebih besar dibandingkan dengan nilai interval kelompok kontrol, dan kemampuan para siswa meningkat setelah treatmen dilaksanakan. Tingkat keefektifitasan yang diperoleh yaitu 0,60 dan dikategorikan sedang. Maka dari itu, tingkat keefektifitasan dari teknik RSS untuk mengajarkan membaca komprehensif teks naratif dalam mata pelajaran Bahasa Inggris pada siswa kelas 10 â€œSMAN 3 Pontianakâ€ tahun ajaran 2014/2015 adalah sedang. Â  Kata Kunci: RSS, Membaca Komprehensif, Teks Naratif.